A Study on Microstructure and Mechanical Properties of Micro Friction Stir Welded Ultra-Thin Al-1060 Sheets by the Shoulderless Tool - Changqing Zhang; Weijie Wang; Xin Jin; Chen Rong; Zhuo Qin (Metals, 2019)
The welding tool is the key of micro friction stir welding (μFSW), which affects the heat input and the plastic forming of weld metal. In this paper, 0.8-mm-thick ultra-thin 1060-H24 aluminum sheets μFSW butt joints were used to compare and analyze the influence of the conventional tool and shoulderless tool on weld shaping, microstructure and mechanical properties. Besides, by measuring the axial force, transverse force and weld temperature in μFSW process, the influence of these two different tools on the heat input and metal flow mechanism of the weld were analyzed. The results show that the weld generated by the shoulderless tool has narrower width, less heat input and metal involved in plastic forming resulting in smaller HAZ (heat affected zone). The hardness of NZ (nugget zone) is obviously increased compared with that of the base metal. The highest tensile strength can reach 108.6 MPa, accounting for 78.6% of the base metal and 117.3% of the joint by the conventional tool. But the welding defects have to be overcome for industrial application of the shoulderless tool.